Protective Effects of Metformin on Doxorubicin-Induced Cardiotoxicity and its Early Detection (Medical Forum Monthly, 2020)
Objective: To evaluate the protective effects of Metformin on Doxorubicin cardiac toxicity and to identify myocardial damage at early phase by quantitative estimation of serum Troponin I (cTnI).Study Design: Randomized lab base studyPlace and Duration of Study: This study was conducted at the Conducted at the Departments of Pharmacology, Army Medical College, Rawalpindi in collaboration with CREAM (Centre for Research in Experimental and Applied Medicine) and completed in four months from April to July 2015.Materials and Methods: Eighteen healthy male adult rabbits randomly divided into three batches were used. Doxorubicin was administered in a group of rabbits to produce cardiotoxicity; while control group received normal saline. The third experimental group got pretreatment for ten days with Metformin before doxorubicin administration.Results: Doxorubicin inflicted marked cardiac damage apparent by elevated serum biomarkers (LDH, CK-MB and cTnI) levels and necrosed cardiomyocytes on histological examination. Metformin pretreatment ensued in decreased serum levels of biomarkers and improved the histological grades of heart tissue.Conclusion: The doxorubicin based chemotherapy can be made efficacious with the concomitant administration of Metformin. The quantitative assessment of serum cTnI for recognition of cardiotoxicity at early stage may direct to substantial financial bearing and improved quality of life in cancer survivors.